Rancangan Aplikasi Sistem Pendukung Keputusan (SPK) Pengangkatan Karyawan Menggunakan Metode Simple Additive Weighting (SAW) Pada PT. Ultra Prima Plast - Flexible Packaging - Dadang Amiruddin; Ely Nuryani; Hani Faturrohmah (Jurnal Sistem Informasi dan Informatika (Simika), 2018)
PT. Ultra Prima Plast - Flexible Packaging always performs a trial period on every new employee. In appointment of new employee candidate required selection process and proper observation during the trial period to maximize the quality of the prospective employee, so far decision-making in the appointment of employees after the completion of the trial period is still done manually by using the assessment of several criteria. The criteria used from the assessment of employee performance are: absenteeism, quality of work, initiative, discipline, responsibility, communication ability and organizational skills. The purpose of holding research on PT. Ultra Prima Plast is to find out what problems or constraints exist in managing employee data, refining existing processes and getting new employee appointments using Simple Additive Weighting (SAW) method. As for data collection methods, the authors used literature study methods, field studies and interviews. In system development, writer use tool (model) of structured system modeling with design tool that is Diagram Unified Modeling Language (UML). Implementation and program design using PHP programming language and MYSQL database. Therefore the authors lift the title "Design Decision Support System (DSS) Application Employee Appointment Using Simple Additive Weighting Method (SAW) At PT. Ultra Prima Plast - Flexible Packaging”